A comparative single dose study of oral acetaminophen 650 mg to its standard 500 mg dose in adult pyrexia patients in a tertiary care hospital - B. T., Pradeepkumar; C. R., Jayanthi; K. R., Raveendra; Y. S., Ramya (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Acetaminophen commonly called as paracetamol is the most used ‘over-the-counter’ analgesic for headache, musculoskeletal pain, dysmenorrhoea etc. It is the best drug to be used as antipyretic for fever due to any cause and safest to be prescribed in all age groups. Antipyretic dose of acetaminophen is 325 to 650 mg; 3 to 4 times a day and is available in the strength of 650 mg and 500 mg tablets. This study was conducted to analyse the antipyretic efficacy and safety profile of two different doses of acetaminophen in patients with low grade fever. Methods: 300 hospitalised patients aged more than 18 years, in department of General Medicine, having low grade fever (38º to 39º C) were randomly allocated into two groups of 150 each, group A received 500 mg and group B received 650 mg of single oral dose of acetaminophen tablets. Oral temperature was measured before dosing, 30 minutes after dosing, one hour, two hourlies thereafter for 6 hours after the dose. Safety was assessed by monitoring for adverse effects during the study and 24 hours after administration of the assigned drug. Results: There was a statistically significant decrease in temperature in group B patients from baseline 39.06±0.87º C to 37.02±0.89º C at the end of 6th hour as compared with 39.18±0.80º C to 38.03±0.77º C in Group A patients (p=0.031). Conclusions: Our study concluded that acetaminophen in a dose of 650 mg is highly efficacious antipyretic drug compared to acetaminophen 500 mg with no adverse effects.